Implementation of phase masking for single molecule tracking in 3D space. (2024)
This project implemented techniques to track single molecules in 3D space inside living cells using a specialized microscope called a light sheet fluorescence microscope. One major challenge was extending the depth range over which molecules could be accurately tracked. To address this, we used a liquid crystal spatial light modulator (SLM) to engineer the point spread function (PSF) of the microscope, which is the image produced by a point source of light. We employed a special "double helix" phase mask pattern to project onto the SLM. This modified the PSF in a way that encoded information about the depth position of the molecule into the shape of the PSF image. Careful alignment and sizing of the phase mask on the SLM was required. Additionally we developed software to automatically detect the positions of single fluorescent particles from the modified PSF images and reconstruct their 3D trajectories over time. This allowed us quantify the diffusion dynamics of the particles, which relates to how molecules move around inside cells. To validate our approach, we measured the diffusion coefficients of fluorescent microbeads suspended in a gel, confirming our method worked accurately. In summary, this phase mask technique coupled with the 3D tracking software enabled extending the depth range for precise single molecule tracking in microscopy of living cells. This could help provide insights into the intricate dynamics underlying biological processes at the molecular level.